The effect of public capital on aggregate output: Empirical evidence for 22 OECD countries - Jan-Erik Wesselhöft (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2013)
Based on new estimates of public and private capital stocks for 22 OECD countries we study the dynamic effect of public capital on the real gross domestic product using a vector autoregression approach. Whereas most former studies put effort on examining the effects of public capital in a single country, this paper covers a large set of OECD countries. The results show that public capital has a positive effect on output in the short-, medium- and long-run in most countries. In countries where the effect is negative, possible explanations as the different productivities of investments, crowding out or high growth rates of government debt are analyzed.
Keywords: C32; E60; H54; 330; Public capital stock; VAR model; Cointegration; OECD countries